Development of an adobe animate-based virtual laboratory for electronic fuel injection practicum - Ghaus Dhiyaurrahman Baunan; Zelhendri Zen; Darmansyah Darmansyah; Rayendra Rayendra (Global Econedu, 2026)
This study developed an Adobe Animate–based virtual laboratory for motorcycle electronic fuel injection practicum in vocational high schools. The study applied the Four-D development model involving define, design, develop, and limited disseminate stages. Data were collected through expert validation sheets, practicality questionnaires, pre-test and post-test, and a motivation questionnaire. Data were analyzed using descriptive percentages, N-gain, and paired-samples t-test. The product was highly valid (89.00%) and highly practical (88.06%). Learning outcomes increased from 61.89 to 89.29, with high N-gain (0.72), improved mastery from 21.4% to 92.9%, and significant test results (t = 8.840; p < .001). Student motivation reached a high category (79.11%). The virtual laboratory is feasible and effective for supporting EFI practicum.